Fluid injection induced seismicity reveals a NE dipping fault in the southeastern sector of the High Agri Valley (southern Italy). Issue 16 (25th August 2014) - Stabile, T. A.; Giocoli, A.; Perrone, A.; Piscitelli, S.; Lapenna, V.
Abstract On 2 June 2006 the wastewater produced during the oil and gas field exploitation in High Agri Valley (southern Italy) started to be managed by disposal through pumping the fluids back into the subsurface at the Costa Molina 2 (CM2) injection well, located in the southeastern sector of the valley. The onset of microearthquakes (Ml ≤ 2) after 4 days at about 1.3 km SW of CM2 well suggests fluid injection induced seismicity by the diffusion of pore pressure. Moreover, the space‐time evolution of 196 high‐resolution relocated events reveals a previously unmapped NE dipping fault. We investigate the physical processes related to the fluid injection induced seismicity and delineate the previously unmapped fault by jointly analyzing seismicity data, geological observations, fluid injection data, the stratigraphic log of the CM2 well, and the electrical resistivity tomography survey carried out in the study area.